Protective effects of taurine on protamine sulfate induced bladder damage - ERCAN, FERİHA; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (SPRINGER, 2006)
The present study was designed to investigate the putative protective effects of taurine on protamine sulfate (PS) induced bladder injury. Wistar albino female rats were catheterized and intravesically infused with phosphate buffered solution (control group) or PS (PS group) dissolved in phosphate buffered solution. In the PS + taurine (PS+Tau) group, after the PS instillation, taurine (50 mg/kg) was injected intraperitoneally for 3 days. Histopathological changes were investigated by light and scanning electron microscopy. Tissue samples were also obtained to determine bladder malondialdehyde (MDA) (a biomarker of oxidative damage) and glutathione (GSH) (a biomarker of protective oxidative injury) levels. In the PS group ulcerated areas, an irregular mucus layer, inflammatory cell infiltration, and increased number of mast cells were observed. In the PS+Tau group, a relatively normal urothelial topography, glycosaminoglycan layer, and decreased number of mucosal mast cells and inflammatory cells were observed. Increased MDA levels as a result of PS induction lead us to propose that free radicals may have a critical role in this injury. The significant decrease in MDA and increase in GSH levels in the PS+Tau group compared to PS group was in accordance with morphological findings. Based on the results, taurine treatment significantly prevented PS induced degenerative morphological and biochemical changes of urinary bladder mucosa.
Keywords: taurine; protamine sulfate; urinary baldder; interstitial cystitis; INTERSTITIAL CYSTITIS; SURFACE GLYCOSAMINOGLYCANS; INDUCED TOXICITY; URINARY-BLADDER; NITRIC-OXIDE; GLUTATHIONE; CHLORAMINE; INJURY